Islamic Bank Marketing Strategy in Increasing Generation Z's Interest in Saving in Islamic Banking Towards the Digital Era - Devi Restiana; Muhammad Iqbal Fasa (Journal of Loomingulisus ja Innovatsioon, 2024)
The increasing adoption of digital technology has changed the way people save and invest their money. Generation Z (born between 1997 and 2012), as the most digitally savvy generation, has different preferences and behaviors when it comes to saving and investing. Islamic banks, in particular, face the challenge of attracting and retaining the savings of the younger generation. The development of sharia banking in the digital era provides opportunities and challenges for its existence. So sharia banks must be able to use existing opportunities as best as possible, namely by improving marketing strategies in the digital era by embracing generation Z. This research aims to identify and analyze strategies carried out by sharia banks to increase generation Z's interest in saving in the era of digitalization. In this research, qualitative methods were used where researchers collected data from existing literature.